2017
DOI: 10.1590/1981-22562017020.160191
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a protocol of Pilates exercises on the contractility of the pelvic floor muscles of non-institutionalized elderly persons

Abstract: Objective: To investigate the influence of a protocol of Pilates exercises on the functionality and contractility of the pelvic floor muscles (PFM) of older women living in the city of Campo Grande, Mato Grosso, Brazil. Method: Ten women (median age of 63.4±4.5 years) with little or no pelvic floor dysfunction were subjected to 24 sessions of Pilates exercises lasting one hour each, for 12 weeks. The pressure of the pelvic floor muscles (PFM) was assessed using a perineometer (cmH 2 0) and contractility was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
5
0
3
Order By: Relevance
“…Pode remeter-se a melhora apresentada pelos idosos nos testes de capacidade funcional, a questão que o Método Pilates é utilizado para promover o reequilíbrio muscular, por meio de exercícios que enfatizam o chamado power house, ou centro do corpo 18 . Este centro diz respeito à região de grupos específicos de músculos (anteriores abdominais, extensores da coluna, extensores do quadril, flexores do quadril e musculatura do assoalho da pelve) 19 . Alguns destes são recrutados em movimentos básicos como caminhar, levantar da posição de decúbito e até mesmo vestir e tirar uma camiseta.…”
Section: Resultsunclassified
“…Pode remeter-se a melhora apresentada pelos idosos nos testes de capacidade funcional, a questão que o Método Pilates é utilizado para promover o reequilíbrio muscular, por meio de exercícios que enfatizam o chamado power house, ou centro do corpo 18 . Este centro diz respeito à região de grupos específicos de músculos (anteriores abdominais, extensores da coluna, extensores do quadril, flexores do quadril e musculatura do assoalho da pelve) 19 . Alguns destes são recrutados em movimentos básicos como caminhar, levantar da posição de decúbito e até mesmo vestir e tirar uma camiseta.…”
Section: Resultsunclassified
“…Given the marked increase in practicing Pilates during pregnancy, various studies have been carried out to evaluate its effectiveness [ 14 , 16 , 20 ]. With regard to the specific relation of Pilates with PFD, two studies found a positive impact on the PF musculature during pregnancy [ 21 , 22 ], while another study concluded that the method was a valid means of helping to prevent the dysfunction [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Force center muscles, also called "powerhouse", refer to the region of specific muscle groups: abdominal muscles, spine extensors, hip extensors, hip flexors, and pelvic floor muscles (PFM) 11 . The recruitment of the "powerhouse" muscles, if well executed, can produce a significant increase in the strength of these muscles 12,13 .…”
Section: Introductionmentioning
confidence: 99%